2018
DOI: 10.1029/2018gl078996
|View full text |Cite
|
Sign up to set email alerts
|

Great Expectations: Plans and Predictions for New Horizons Encounter With Kuiper Belt Object 2014 MU69 (“Ultima Thule”)

Abstract: The New Horizons encounter with the cold classical Kuiper Belt object 2014 MU69 (informally named “Ultima Thule,” hereafter Ultima) on 1 January 2019 will be the first time a spacecraft has ever closely observed one of the free‐orbiting small denizens of the Kuiper Belt. Related to but not thought to have formed in the same region of the solar system as the comets that been explored so far, it will also be the most distant, and most primitive body yet visited by spacecraft. In this letter we begin with a brief… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Also, in Thirouin & Sheppard (2019), we report several potential contact binaries showing a large lightcurve amplitude but unfortunately without a full lightcurve allowing us to classify them as likely/confirmed contact binaries, and thus to be conservative we consider them as potential contact binaries as more data are needed to classify them. Finally, the flyby of 2014 MU 69 by the NASA New Horizons spacecraft and its stellar occultation confirmed that this dynamically Cold Classical trans-Neptunian object (TNO) is also a contact binary (Stern et al 2019;Moore et al 2018). Currently, the census of contact binaries is: .…”
Section: Contact Binariesmentioning
confidence: 86%
“…Also, in Thirouin & Sheppard (2019), we report several potential contact binaries showing a large lightcurve amplitude but unfortunately without a full lightcurve allowing us to classify them as likely/confirmed contact binaries, and thus to be conservative we consider them as potential contact binaries as more data are needed to classify them. Finally, the flyby of 2014 MU 69 by the NASA New Horizons spacecraft and its stellar occultation confirmed that this dynamically Cold Classical trans-Neptunian object (TNO) is also a contact binary (Stern et al 2019;Moore et al 2018). Currently, the census of contact binaries is: .…”
Section: Contact Binariesmentioning
confidence: 86%
“…The upcoming flyby of the New Horizons spacecraft by the cold classical transneptunian object (TNO) 2014 MU69 (hereafter referred to as MU69) will offer the first up-close look (sub-km resolution) of a small outer Solar System body in its formation environment, and will provide the first opportunity to observe a high-resolution cratered surface of a TNO other than those in the Pluto system, imaged by New Horizons in July 2015 (Stern et al, 2015;Moore et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…and 𝑚𝑅 4 ' 𝜔6 , respectively, where m and Re are the total mass and equivalent spherical radius. The normalized spin and angular momentum for Arrokoth are ~0.29 and ~0.36, respectively, assuming a mass ratio of 2:1 for LL and SL and r = 500 kg m -3 for both lobes.…”
mentioning
confidence: 99%